THE STUDENTS PERCEPTIONS ON A TEST OF ENGLISH PROFICIENCY AS GRADUATION REQUIREMENT - Rohman, Kacung Arif (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2019)
TEP, Test of English Proficiency, is a type of English test which is held regularly by Language Center (LC) of Universitas Swadaya Gunung Jati (UGJ) Cirebon based on the Rectors decree as policy. It becomes one of the requirements for the students who are going to graduate from higher education. This research intends to 1) explore the students perception on a Test of English Proficiency and 2) find out about how is the implementation of TEP. The writers conducted a case study with 288 students as the respondents. They come from different majors and faculties. There are four techniques of collecting data: 1) interviews, 2) observation, 3) questionnaires, and 4) documents. To get the valid data, the writers used triangulation of sources to cross check and compare data. An interactive model (data collection, data display, data reduction, and conclusion) is used to analyze data. The research findings reveal that the students perceptions on TEP can be classified into three aspects: TEP activity, test instrument, and preparation while the implementation of TEP such as a registration system, information system, proctoring, and facilities get satisfactory responses from the students.